Koncepcja sprawiedliwości Gustava Radbrucha - Bieczyński, Mateusz Maria (Civitas. Studia z filozofii polityki, 2011)
The author undertakes an attempt to present the philosophical and legal concepts comprising the legacy of a German theoretician of law, Gustav Radbruch, in respect of justice. The historical context for Radbruch is World War II, which forced German lawyers to face the question of the limits to which positive law is binding. Radbruch’s theory makes a breach in the legal positivism current of German legal reflection and thus belongs to what is known as the third way, setting out new prospects in the history of the philosophy of law. The thread described by the author is the manner in which Radbruch connects natural law with legal positivism, demonstrating that, within a legal reality, they may exist in parallel.